Mortality Rates After Posterior C1–2 Fusion for Displaced Type II Odontoid Fractures in Octogenarians. Issue 18 (15th September 2018) - Clark, Stephen; Nash, Alysa; Shasti, Mark; Brown, Luke; Jauregui, Julio J.; Mistretta, Katherine; Koh, Eugene; Banagan, Kelley; Ludwig, Steven; Gelb, Daniel
Abstract : Study Design: Retrospective cohort study Objective: To assess 30-day and 1-year mortality rates as well as the most common complications associated with posterior C1–2 fusion in an octogenarian cohort. Summary of Background Data: Treatment of unstable type II odontoid fractures in elderly patients can present challenges. Recent evidence indicates in patients older than 80 years, posterior C1–2 fusion results in improved survival as compared to other modes of treatment. Methods: Retrospective analysis of 43 consecutive patients (25 female and 18 male; mean age 84.3 yr, range 80–89 yr; mean Charlson Comorbidity Index 1.4, (range 1–6); mean body mass index 24.8 ± 4.2 kg/m 2, who underwent posterior C1-C2 fusion for management of unstable type II odontoid fracture by four fellowship trained spine surgeons at a single institution between January 2006 to June 2016. Results: Mean fracture displacement was 5.1 ± 3.6 mm and mean absolute value of angulation was 19.93° ± 12.93°. The most common complications were altered mental status (41.9%, n = 18), dysphagia (27.9%, n = 12) with 50% of those patients (6/12) requiring a feeding tube, and emergency reintubation (9.3%, n = 4). To the date of review completion, 25 of 43 patients expired (58.1%), median survival of 1.76 years from the date of surgery. Thirty-day and 1-year mortality rates were 2.3% and 18.6%, respectively. Patients who developed dysphagia were 14.5 times more likely to have expired at 1 year; dysphagia was also found to be significantly associated with degree of displacement. Fracture displacement was found to be associated with increased odds for 1-year mortality when accounting for age and requirement of a feeding tube. Conclusion: Posterior C1–2 fusion results in acceptably low mortality rates in octogenarians with unstable type II odontoid fractures when compared to nonoperative management mortality rates in current literature. Initial fracture displacement is associated with higher mortality rate in this patient population. Level of Evidence: 4